BRANDEDTOURIST PRODUCTS IN THE PROMOTIONAL OPERATIONS OF SELECTED NATIONAL TOURISM ORGANIZATIONS (NTO) (Research Bulletins of the Faculty of Economic Sciences, 2021)
In the article, the role of the brand and tourist branded products was defined in the promotional activities that are undertaken by the National Tourism Organizations of selected countries (i.e. Austria, the Czech Republic, France, Spain, Germany, Poland, Serbia). The idea of the functioning of National Tourism Organizations as well as the main objectives and tasks of this type institutions in the individual states were alsode-scribed. In particular, examples were presented of promotional campaigns, that use specific tourist branded products for the promotion of a given country. In the article, the following research thesis was accepted, i.e. tourist branded products constitute the basis of promotional campaigns realized by the National Tourist Organizations.
Keywords: brand,branded product, the National Tourist Organization, promotion, pro-motional campaign